The Effect of Aging Consumers’ Characteristics on Store Selection and Food Shopping: A Review - Verma, Vimal Chandra (Animo Repository, 2022)
The human population is aging faster and faster than in the past. As a result, it can be demographically proven that there will be more people older than 60 worldwide in the next 35 years. According to the United Nations Population Fund’s (UNFPA’s) India Aging Report 2017, the proportion of people over 60 could increase from 8% in 2015 to 19% in 2050. The Indian government in particular states in its report that there will be 340 million people over 60 by 2050, creating new challenges due to specific characteristics and needs. However, this often overlooks the group of older consumers who make up a significant part of the world’s annually growing population. Therefore, this paper explores the general characteristics of older consumers, their latent needs, and factors that influence their food choices. This is done through thorough literature review using secondary sources to identify factors influencing food shopping and shop selection among older consumers in India.